A systematic review and meta‐analysis of non‐adherence to anti‐diabetic medication: Evidence from low‐ and middle‐income countries. Issue 11 (23rd August 2021) - Azharuddin, Md; Adil, Mohammad; Sharma, Manju; Gyawali, Bishal
Abstract: Background: Non‐adherence to anti‐diabetic medication is an important cause of uncontrolled blood glucose that leads to complications of diabetes. However, there is a lack of evidence on the burden of and factors associated with non‐adherence to anti‐diabetic medication among individuals living with diabetes in low‐and middle‐income countries (LMICs). Objectives: This systematic literature review and meta‐analytic synthesis aims to estimate non‐adherence to anti‐diabetic medication reported among individuals in LMICs and explores factors affecting non‐adherence. Methods: We systematically searched MEDLINE and Embase to identify studies investigating non‐adherence to anti‐diabetic medications published from January 2000 to May 2020. Two authors carried out study selection, screening, and data extraction independently. Cross‐sectional studies that had been conducted among individuals with diabetes in LMICs were eligible for the selection process. Critical appraisal of the included studies was carried out using the Newcastle Ottawa Scale. Meta‐analysis was carried out using Stata 14.2. Random effects model was used to compute the pooled proportion at a 95% confidence interval (CI). Results: Forty‐three studies met the inclusion criteria, of which 13 studies were used in meta‐analysis. The pooled proportion of non‐adherence to anti‐diabetic medications using the eight‐item Morisky Medication Adherence Scale (MMAS‐8) was 43.4% (95% CI: 17.5‐69.4; P  < 0.001) and 29.1% (95% CI: 19.8‐38.4; P  < 0.001) when using the cut‐off at 80 or 90%. The pooled proportion of non‐adherence was 29.5% (95% CI: 25.5‐33.5; P  = .098) when using the four‐item Morisky Medication Adherence Scale (MMAS‐4). Using the World Health Organization (WHO) five dimensions of medication adherence framework, the factors contributing to non‐adherence were varied, including disease factors, therapy‐related factors, healthcare system factor, patient‐centred factors, and socio‐economic factors. Conclusions: Non‐adherence to anti‐diabetic medication remains an ongoing challenge in LMICs and several factors operating at different levels were cited as reasons. Comprehensive intervention strategies are urgently needed to address these factors in effectively tackling medication non‐adherence in LMICs.